Sickness absence due to Covid test obligations in the workplace - Susanne Wanger; Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
As vaccines for Covid-19 became available, in 2021 many countries introduced an obligation for employees to provide proof of their Covid status in the workplace, in Germany also known as the 3G rule (vaccinated, recovered, tested). In view of the controversial debate, concerns arose that employees might attempt to circumvent this obligation by taking sick leave. For an empirical panel analysis we combine data from health insurance providers with epidemiological data for the German federal states. In fact, our findings do show that - while controlling for infection rates - a one percentage-point lower vaccination rate led to an increase in the sickness absence rate by 0.021 percentage points when the 3G rule came into effect. – – Mit der Verfügbarkeit von Corona-Impfstoffen führten viele Länder im Jahr 2021 die Verpflichtung ein, am Arbeitsplatz Impf-, Genesenen- oder Testzertifikate nachzuweisen, in Deutschland auch bekannt als 3G-Regel (geimpft, genesen, getestet). Angesichts der kontroversen Debatten wurden Befürchtungen laut, dass Beschäftigte versuchen könnten, sich dieser Nachweispflicht zu entziehen, indem sie sich krankschreiben lassen. Für eine empirische Panel-Analyse kombinieren wir Krankenkassendaten und epidemiologische Daten für die deutschen Bundesländer. In der Tat zeigen unsere Ergebnisse, dass - unter Kontrolle der Infektionsinzidenz - eine um einen Prozentpunkt niedrigere Impfquote mit Inkrafttreten von 3G zu einem um 0,021 Prozentpunkte höheren Krankenstand führte.
Keywords: H12; I10; J81; 330; Covid-status certification; Covid-19; Sick leave; Workplace